Socio-cultural context, child development and beginning reading in Peru - Thorne, Cecilia (2005)
This article focuses on the fact that many children in Peru are not able to read fluently when they finish elementary school. To analyze this shortcoming it presents an overview of the Peruvian context, the education system, the multilingual and the socio-cultural background and identifies the difficult conditions in which Peruvian children grow and its consequences in child development and beginning reading. The paper discusses different aspectsof developmental psychology and puts the accent on Bronfenbrenner's theory and the developmental approach to education. It offers, also, a review of several studies on reading in Peru. Finally it emphasizes the advantages of incorporating the ecological theory and the developmental approach to education